Penerapan Segmenting, Targeting, Dan Positioning Pada Perumahan Graha Asri Residence - Mohamad Ulinnuha (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
In essence, housing is intended to meet basic needs for space, where humans can take shelter, take refuge, and live in society. In line with meeting these basic needs, functional housing development can support economic development and provide direction for the growth of a region. On the basis of an analysis of the high economic growth of the Karawang district in 2011 to 2019, it is directly proportional to the growth of its population, which has reached 2.3 million people, not including millions of immigrants or immigrants. It is clear from this that the demand for housing products continues to grow. Thus, business real estate in Karawang continues to grow and is very promising at that time. Thus it is necessary to hold observations or case studies to find out the applicationSegmenting, Targeting, and Positioning which is right at Graha Asri housingResidence and to find out the right steps and what to do next to achieve the company's goals. And it turns out that from the results of observations that have been made by the practical work participants, it turns out that those that lead to the negative are in the categoryTargeting (Target), this is due to the policy of the Karawang district government which deliberately restricts new arrivals because it aims to prioritize local communities so they are more productive in their own city.